2018
DOI: 10.1039/c8ja00095f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microwave-assisted ultraviolet digestion method for biodiesel and subsequent trace elements determination by SF-ICP-MS

Abstract: A microwave-assisted ultraviolet digestion (MW-UV) method for biodiesel is proposed for subsequent determination of Ba, Co, Cr, Cu, Mn, Ni, Pb, Sr, and V by sector field inductively coupled plasma mass spectrometry (SF-ICP-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… SRM 1634c MA-HPD Ba, Na, Ni and V 9 mL of 5 M H 2 O 2 and 1 mL of conc. HNO 3 0.55–58.86 104.8–117.7 ≤ 4.1 0.046, 0.0304,0.408 and 0.057 ICP-OES This work Biodiesel MAAD Ba, Ni and V 10 mL of 7 M HNO 3 0.0027–0.101 95–108 < 6 0.00012,0.0028 and 0.00012 SF-ICP-MS 20 Crude oil MAAD Mg, Pb and Sr 6 mL of 14.4 M of HNO 3 Mg (12.5–201), Pb (0.09–0.203) and Sr (2.3–6.06) 95–104 < 4.0 0.1,0.3 and 0.07 MI-ICP-MS 36 Crude oil MAAD Na, Ca and Mg 4 M of H 2 O 2 and 5 mL conc. HNO 3 0.003–22.6 94–110 < 5 0.001–0.002 ICP-OES 5 Crude oil MAAD Ni and V 5 mL of 4 M H 2 O 2 and 10 mL of 5 M HNO 3 2–230 94.6–98.2 < 4.62 0.237 and 0.060 ICP-OES 37 Diesel MAAD Al, Cu, Fe, Ni and Ni 4 mL conc.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“… SRM 1634c MA-HPD Ba, Na, Ni and V 9 mL of 5 M H 2 O 2 and 1 mL of conc. HNO 3 0.55–58.86 104.8–117.7 ≤ 4.1 0.046, 0.0304,0.408 and 0.057 ICP-OES This work Biodiesel MAAD Ba, Ni and V 10 mL of 7 M HNO 3 0.0027–0.101 95–108 < 6 0.00012,0.0028 and 0.00012 SF-ICP-MS 20 Crude oil MAAD Mg, Pb and Sr 6 mL of 14.4 M of HNO 3 Mg (12.5–201), Pb (0.09–0.203) and Sr (2.3–6.06) 95–104 < 4.0 0.1,0.3 and 0.07 MI-ICP-MS 36 Crude oil MAAD Na, Ca and Mg 4 M of H 2 O 2 and 5 mL conc. HNO 3 0.003–22.6 94–110 < 5 0.001–0.002 ICP-OES 5 Crude oil MAAD Ni and V 5 mL of 4 M H 2 O 2 and 10 mL of 5 M HNO 3 2–230 94.6–98.2 < 4.62 0.237 and 0.060 ICP-OES 37 Diesel MAAD Al, Cu, Fe, Ni and Ni 4 mL conc.…”
Section: Resultsmentioning
confidence: 94%
“…However, when comparing the reagents used, the current study used a much environmentally friendly method as the 1 mL concentrated acid when put in the reagent solution was much dilute (1.58 M). Another study reported by Barela et al 20 on the digestion of biodiesel for determination of Ba, Co, Cr, Mn, Ni, Pb, Sr and V prior to analysis using SF-ICP-MS. This method reported very good accuracy (95–108%), precision (< 6%), and MDL (0.12, 2.8 and 0.12 ng/g) for Ba, Ni and V respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations